Factores que delimitan la participación activa en los proceso de enseñanza-aprendizaje de las clases virtuales en los estudiantes de octavo año de básica de la Unidad Educativa Barreiro periodo 2021-2022 - Rosado Caicedo, Cindy Lilibeth (2023)
Teaching and learning from virtuality today requires teachers capable of transforming their pedagogy using new information and communication technologies (ICT) to serve their students and face the challenges in the educational context and the factors that limit active participation in the teaching-learning process of virtual classes for eighth-year students of the Barreiro Educational Unit, period 2021-2022. In addition, the collaboration of the students is a fundamental factor to improve the quality of learning, therefore, qualitative and quantitative research was used, through the survey technique where questionnaires were applied to students and teachers using the google form tool that allowed automation of responses. Likewise, the results reveal that the teacher grants them the intervention of the students in the classroom, but they expect it to happen at their request. They are not in the teacher's plans to involve in active participation, and inclusion this would improve their academic performance. Students also recognize the importance of ensuring their learning, but expect their teachers to encourage them. On the other, this is an invitation to institutions to promote the importance of active pedagogy in the classroom, since it is a central axis of quality learning, which teachers in their practice are expected to promote a transformative pedagogical education that can awaken in the group of students the motivation to learn actively and according to the advances that society presents.